PERBANDINGAN INTONASI DAN DURASI UJARAN MASAK SIH ANTARA PENUTUR LAKI-LAKI DAN PEREMPUAN - Wawan Prihartono (Balai Bahasa Provinsi Papua, 2019)
The accoustic feature of an utterance is particularly influenced by its contexts and gender of the speaker. One tends to speak in low intensity, low pitch, long duration and flat tone even low, when they were sad. On the contrary, when one gets angry, s/he will speak in high intensity and pitch as well as her/his tone. Then, its duration is probably sharp. utterance character of male is highly diferent with female one due to their physiology form of speech organ. This study will evident that assumption by comparing between male and female of the utterance of masak sih using acoustic phonetics theory. The result shows that male would rather give low frequency for this utterance than female did. The duration of this utterance is, however, relatively similar between male and female.